Why? How Perpetrators of Male-Male Homicide Explain the Crime - Di Marco, Martín Hernán (Journal of interpersonal violence, 2023)
This paper identifies the explanatory narratives used by perpetrators of male-male homicide in Buenos Aires (Argentina) to make sense of this crime. Drawing upon narrative criminology and masculinities theories, this study enquires into the rationalisations of perpetrators, considering their emic terms, rationalities and stories. Fieldwork was conducted between 2016 and 2020, and a convenience sample strategy was employed for participant recruitment. The analysis is based upon seventy-three narrative-biographical interviews with offenders, and field observations in prisons and homes of former convicts. The corpus was analysed following an inductive thematic coding strategy using Atlas.Ti. Eight narratives were typified, considering how men talked about agency and change, and the explanatory locus of the stories: ‘rebel’, ‘affected’, ‘idiot’, ‘either him or me’, ‘repeating the story’, ‘gang’, ‘betrayed’ and ‘victim’. These accounts revealed two paradoxes about violence perpetration storytelling and its discursive management: men can commit a homicide and present themselves as not responsible for it and, simultaneously, they use, reconfigure and negotiate expert theories and scientific labels to explain away, excuse and justify lethal violence. This study argues that accounts are not merely neutralisation strategies, but the rationalisations of the perpetrators’ experiences, and the foundation for how they relate to and inhabit penal institutions. This paper contributes to the understanding of how those explanations shape past and future actions, and how masculinities, biographical processes and violence performance are interconnected.